Targeting the fibroblast growth factor receptor family in cancer. (May 2016) - Hallinan, Niamh; Finn, Stephen; Cuffe, Sinead; Rafee, Shereen; O'Byrne, Kenneth; Gately, Kathy
Highlights: Deregulation of the FGF/FGFR signalling axis is observed in a wide variety of human carcinomas. FGFR and EGFR pathways offer a compensatory signalling escape mechanism when either is inhibited. Co-activation of c-MET and FGFR has been observed in several cancer cell lines. Dual FGFR kinase targeting inhibitors such as FIIN-3 may be able to overcome clinical resistance. Co-targeting FGFR pathway and a parallel proliferative pathway may overcome clinical resistance. Abstract: Fibroblast growth factors (FGFs) regulate a plethora of biological functions, in both the embryonic and adult stages of development, binding their cognate receptors and thus activating a variety of downstream signalling pathways. Deregulation of the FGF/FGFR signalling axis, observed in multifarious tumor types including squamous non-small cell lung cancer, occurs through genomic FGFR alterations that drive ligand-independent receptor signalling or alterations that support ligand-dependent activation. Mutations are not restricted to the tyrosine kinase domain and aberrations appear to be tumor type dependent. As well as its complementarity and synergy with VEGF of particular interest is the interplay between FGFR and EGFR and the ability of these pathways to offer a compensatory signalling escape mechanism when either is inhibited. Hence there exists a rationale for a combinatorial approach to inhibition of these dysregulated pathways to reverse drug resistance. To date, several multi-target tyrosine kinase inhibitors as well as FGFR specific tyrosine kinase inhibitors (TKIs), monoclonal antibodies and FGF ligand traps have been developed. Promising preclinical data has resulted in several drugs entering clinical trials. This review explores aberrant FGFR and its potential as a therapeutic target in solid tumors.